2000
DOI: 10.1007/s004490000200
|View full text |Cite
|
Sign up to set email alerts
|

Fed-batch cultivation of Acetobacter suboxydans for the microbial oxidation of D-sorbitol to L-sorbose

Abstract: Microbial oxidation of D-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Other l -ketoses have been synthesized in this manner such as l -tagatose ( 31 ) by microbial oxidation of galactitol ( 506 ), , l -fructose ( 475 ) from l -mannitol ( 176 ), l -psicose ( 479 ) from allitol ( 507 ), and obviously l -sorbose ( 452 ) by oxidation of sorbitol ( 508 ) (Scheme ) . There is considerable literature on the latter process as it is the first step of a two-step biotechnological process for preparation of vitamin C from 508 . Many smart developments such as immobilized organisms, thermoresistant strains, fed-batch methods, continuous fermentation, computer-coupled substrate feeding, and using oxygen vectors have been reported. Yields are frequently over 90%, but byproducts such as d -fructose and d -mannitol can be formed, and rates can be limited …”
Section: Chemoenzymatic Synthesis Of L-hexosesmentioning
confidence: 99%
“…Other l -ketoses have been synthesized in this manner such as l -tagatose ( 31 ) by microbial oxidation of galactitol ( 506 ), , l -fructose ( 475 ) from l -mannitol ( 176 ), l -psicose ( 479 ) from allitol ( 507 ), and obviously l -sorbose ( 452 ) by oxidation of sorbitol ( 508 ) (Scheme ) . There is considerable literature on the latter process as it is the first step of a two-step biotechnological process for preparation of vitamin C from 508 . Many smart developments such as immobilized organisms, thermoresistant strains, fed-batch methods, continuous fermentation, computer-coupled substrate feeding, and using oxygen vectors have been reported. Yields are frequently over 90%, but byproducts such as d -fructose and d -mannitol can be formed, and rates can be limited …”
Section: Chemoenzymatic Synthesis Of L-hexosesmentioning
confidence: 99%
“…Furthermore, it was shown that the effect of growth inhibition by DHA was stronger compared to other products such as L-sorbose. According to Giridhar and Srivastava [13], the cells were able to grow even at a L-sorbose concentration of 200 kg m À3 . However, a literature survey revealed that the state of knowledge on the regeneration capability of G. oxydans in dependence of the DHA concentration is low.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved oxygen was also an important factor in the fermentation process of vitamin C. Giridhar and Srivastava ( 2000 ) found that in the batch and fed-batch fermentation processes of D-sorbitol to L-sorbose, adding 4% of the oxygen vector (N-hexadecane) could shorten the period for 2 and 5 h, and increase the production by 17 and 26%, respectively.…”
Section: Previous Research On the Classical Two-step Fermentation Promentioning
confidence: 98%